An Empirical Analysis of Profitability Determinants in Chinese Banking System - Jin, Chong (2018)
The aim of this dissertation is to investigate the potential variables which have an impact on bank performance in Chinese banking system over the period 2011-2017, by using a dynamic panel data model, System Generalized Method of Moments (SGMM). The results indicate that GDP growth rate, unemployment rate, loan loss provision to gross loan and loans to total assets have a significantly positive impact on bank profitability performance while cost to income, impaired loan to gross loan and loan to deposits have an adverse influence on bank performance. In addition, equity to total assets, bank size and inflation rate does not show a significant impact on bank profitability.